(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Genetic algorithms have widely been used in optimization tasks, and there are only a few works that use genetic algorithms to find rules.